Fire and Ice : The Poetry of Xavier Villaurrutia - Forster, Merlin H. (North Carolina studies in the Romance languages and literatures. Essays, 2019)
This study presents the poetry of Xavier Villarrutia, analyzing it on several levels. The book moves from the specific to the more abstract, from commentary on lexicon and syntax, through metrics and figurative language, to a consideration of the poet's major themes: love, death, and oppressive solitude. The final section is an evaluation of the place of Villarrutia's poetry, and of the author himself, in both Mexican literature and in the larger Western tradition.